Quaternized chitosan mediated assembly of gold nanoparticles multilayers - Bracamonte, Maria Victoria (2014)
Self-assembled multilayers of quaternized chitosan (QCHI) and gold nanoparticles (AuNPs) were built up on quartz and gold substrates. To evaluate the effect of the surface coverage of AuNPs on the structural, optical and electrochemical properties of multilayers prepared with different AuNPs adsorption time were compared. UV-Vis and AFM characterization indicated that AuNPs in each bilayer are spatially separated, and interparticle interactions are mainly produced between bilayers. The complex refractive index and thickness of the QCHI-AuNPs multilayers were properly determined using an anisotropic single layer model. The optical constants obtained were quite different from those of bulk gold, and their values depend on the coverage of AuNPs. The thickness per bilayer of the structures present a progressive increase as AuNP's coverage augments, reaching a value close to the nominal AuNPs diameter after 60 min of adsorption. These results indicate that the interpenetration of bilayers in the structure depends on the surface concentration of AuNPs. The charge transport through the QCHI-AuNPs film was studied using different redox probes. The effects of the adsorption time of AuNPs and the number of bilayers (n) of the structure on the charge transfer rate constants, kct, were analyzed. The incorporation of AuNPs in the structure produces an increase of kct, as the adsorption time of AuNPs rise. In addition, the values of kct were independent of n, in the interval studied (up to n = 5), suggesting that the electronic communication in the multilayered structure was mediated by the AuNPs.